2007
DOI: 10.1007/s10753-007-9025-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammation Role for Mesenchymal Stem Cells Transplantation in Myocardial Infarction

Abstract: The aim of the present study was to investigate the role of anti-inflammation for MSCs transplantation in rat models of myocardial infarction. Rats with AMI induced by occlusion of the left coronary artery were randomized to MSCs transplantation group, MI group and sham operated group. The effects of MSCs transplantation on cardiac inflammation and left ventricular remodeling in non-infarcted zone were observed after 4 weeks of MI. We found that MSC transplantation (1) decreased protein production and gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
87
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 29 publications
14
87
0
1
Order By: Relevance
“…Recent animal studies in a model of experimental autoimmune encephalomyelitis demonstrated that MSC treatment results in a significantly milder disease and fewer relapses compared with control mice, with a decreased number of inflammatory infiltrates and reduced demyelination and axonal loss (Gerdoni et al, 2007;Zappia et al, 2005). Additionally, Guo et al (2007) reported that MSC transplantation decreases protein production and gene expression of inflammation cytokines and increases functional recovery from myocardial infarcts. These studies suggest that the anti-inflammatory actions of MSCs may be one underlying mechanism of the tissue-protective effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent animal studies in a model of experimental autoimmune encephalomyelitis demonstrated that MSC treatment results in a significantly milder disease and fewer relapses compared with control mice, with a decreased number of inflammatory infiltrates and reduced demyelination and axonal loss (Gerdoni et al, 2007;Zappia et al, 2005). Additionally, Guo et al (2007) reported that MSC transplantation decreases protein production and gene expression of inflammation cytokines and increases functional recovery from myocardial infarcts. These studies suggest that the anti-inflammatory actions of MSCs may be one underlying mechanism of the tissue-protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the neuroprotective effect of MSCs may be mediated not only by their differentiation into neuron-like cells, but also by their ability to produce various trophic factors that may contribute to functional recovery, neuronal cell survival, and stimulation of endogenous regeneration (Barry and Murphy, 2004). Of these, the anti-inflammatory role of MSCs in cell transplantation as a protective mechanism has been demonstrated in vitro and in animal models of ischemic heart disease and experimental autoimmune encephalomyelitis (Gerdoni et al, 2007;Guo et al, 2007;Zappia et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their therapeutic effect did not appear to result from their direct integration into or reconstitution of host tissues. Rather, it now appears that MSCs promote tissue repair by secreting soluble factors that block apoptosis, [20][21][22] inflammation, [23][24][25][26] other immune cell-mediated responses, 27 and also stimulate the growth of host cells. 28 Therefore, the cells appear to function in tissue repair in a manner similar to their well established role in regulating hematopoiesis in bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have attracted significant attention as a potential therapeutic agent for tissue repair due to their ability to migrate to the damaged tissue. 6,7 Recent experimental studies have showed that MSC can efficiently attenuate inflammatory processes, for instance, myocardial infarction 8 and acute lung injury. 9 It was shown that MSC transplantation in a rat model of myocardial infarction decreased the expression of inflammatory cytokines such as TNF-α, IL-1β, and IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…9 It was shown that MSC transplantation in a rat model of myocardial infarction decreased the expression of inflammatory cytokines such as TNF-α, IL-1β, and IL-6. 8 In an acute lung injury model, it was observed that MSC therapy reduced the levels of pro-inflammatory cytokines, increased the level of antiinflammatory cytokines in the plasma and bronchoalveolar lavage. 9 We aimed to determine the effect of MSC transplantation on the peritoneal morphology and inflammation markers in rat models of PD.…”
Section: Introductionmentioning
confidence: 99%